Tempo e conhecimento: entre Merleau-Ponty e Claudel - Santana, Cleiton Nery de (2021)
The research aims to identify possible relationships between Merleau-Ponty and Claudel through the concepts of time and knowledge. For this purpose, we will first look at the relationship between philosophy and non-philosophy, which appears in the philosopher's last courses at the Collège de France. To further circumscribe the issue, we will then move from the concept of non-philosophy to that of literature that Merleau-Ponty particularly thematized in his texts and courses during the fifties. We will see that the 1960-1961 course on ontology includes lessons on Claudel's thought. It will help understand the crucial role Claudel played in Merleau-Ponty’s philosophical project. In the second part, we will examine the poetic and philosophical descriptions of the concept of time. After presenting Claudel’s notion of time, as defined in his Art Poétique, we will look at the same notion in Merleau-Ponty. It is our working hypothesis that possible relationships exist between them both. Our third and last part will first explore Claudel’s concept of knowledge (connaissance), before turning to the very same concept in Merleau-Ponty, in both his phenomenological and ontological phases. We will conclude by showing that the notions of knowledge, in both Merleau-Ponty and Claudel, invade (empiétement) and involve (Ineinander) each other